High-specific-energy lithium storage positive electrode, integrated composite modification method thereof and solid-state battery prepared from high-specific-energy lithium storage positive electrode
By coating nano-oxides and blending ceramic electrolytes on the surface of the high-specific energy lithium storage cathode material, and building a ceramic coating to form an integrated composite modified cathode, the problems of sudden drop in specific energy and safety hazards of lithium storage cathode material in the early stage of circulation are solved, and the performance and safety improvement of high-specific energy solid-state batteries are achieved.
Patent Information
- Application Number
- CN202411732560.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
High-performance lithium storage cathode materials will experience a sharp drop in specific energy, increase in impedance, and decay failure in the early stages of the cycle, resulting in battery polarization, heating and failure. The active metal elements are prone to react with solid electrolytes, resulting in structural phase transformation and safety hazards.
Using an integrated composite modification method, nano-oxide coating is carried out on the surface of the particles of the high-specific energy storage lithium positive electrode material, ceramic electrolyte is blended internally, and a ceramic coating is constructed on the surface to form an integrated composite modified positive electrode.
It effectively improves the ion transport performance and thermal stability of the interface of the positive electrode and electrode layer of high specific energy storage, suppresses the safety problems caused by electrochemical instability and oxygen evolution, and improves the performance and safety of high specific energy solid-state batteries.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of chemical power sources, and in particular relates to a high-energy-density lithium storage positive electrode and an integrated composite modification method thereof and a prepared solid-state battery. Background Art
[0002] In order to meet the increasingly urgent application requirements for high energy density, safety and reliability of energy storage batteries, high specific energy solid-state battery technology has been widely studied. Among them, high specific energy storage lithium cathode materials are the basis for obtaining high specific energy of batteries, and research hotspots include high nickel materials (NCA, NCM) and lithium-rich manganese-based (LRM) materials.
[0003] However, high-performance lithium storage cathode materials have poor structural stability. The solid solution or layered structure makes the material metastable in a high-valence state. The irreversible release of lattice oxygen causes the material to change phase, which hinders the insertion of lithium into the material, resulting in a significant decrease in the material's ability to insert lithium, and a significant decrease in the material's specific capacity and operating voltage. Therefore, high-performance lithium storage cathode materials will experience a sudden drop in specific energy, increased impedance, and decay failure at the beginning of the cycle, leading to battery polarization, heating, and failure. High-performance lithium storage cathode materials have an extremely high content of active metal elements, so the material is highly active and easily reacts with solid electrolytes, inducing the material to undergo irreversible release of lattice oxygen, accelerating the internal structural phase change of the material, and the release of lattice oxygen ions will react with the solid electrolyte, further accelerating the material instability and battery failure process. Summary of the invention
[0004] The technical problem to be solved by the present invention is a high-energy-density lithium storage positive electrode and its integrated composite modification method and the solid-state battery prepared, which effectively improves the high-energy-density lithium storage positive electrode and the interface ion transport performance and thermal stability of the electrode layer, inhibits electrochemical instability and safety problems caused by oxygen evolution, thereby achieving performance improvement of high-energy-density solid-state batteries.
[0005] The technical solution adopted by the present invention is: an integrated composite modification method for a high specific energy lithium storage positive electrode, comprising the following steps:
[0006] (1) coating the surface of high specific energy lithium storage cathode material particles with nano-oxide materials;
[0007] (2) blending a ceramic electrolyte inside the coated positive electrode layer to form a composite positive electrode layer;
[0008] (3) A ceramic coating is constructed on the surface of the composite positive electrode layer to form an integrated composite modified high energy density lithium storage positive electrode.
[0009] The nano-oxide coating layer in step (1) is composed of aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), zirconium dioxide (ZrO2), tantalum oxide (LiTaO3, Li3TaO4), Li 1.3 Ti 1.7 Al 0.3 One or more combinations of (PO4)3, the coating method is solid phase method, liquid phase method, ALD method, and the coating layer thickness is 2-50nm.
[0010] The ceramic components in the ceramic electrolyte in step (2) and the ceramic coating in step (3) are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), zirconium dioxide (ZrO2), tantalum oxide (LiTaO3, Li3TaO4), Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 3α La 2 / 3-α TiO3, Li 1.3 Ti 1.7 Al 0.3 (PO4)3, Li 1+β Al β Ge 2-β ( PO4)3, Li 4-δ Ge 1-δ P δ S4, Li7P2S8I, Li2S-P2S5, Li6PS5Cl, one or more combinations thereof, wherein 0.01≤α≤0.33, 0≤β≤0.65, 0≤δ≤1, X=F, Cl, Br, I; the ceramic electrolyte component accounts for 1%-25% of the electrode mass, and the compaction density of the composite electrode after blending is 2.5-3.4g / cm 3 .
[0011] The method for constructing the ceramic coating in step (3) is ultrasonic spraying, the precursor slurry is a ceramic material slurry, the slurry composition is ceramic material, N-methyl-2-pyrrolidone (NMP) solvent and PVDF-HFP glue, the ceramic particle size is 50-500nm, the ceramic content is 3%-7%, and the glue content is 0.5%-2%; the vacuum drying temperature after spraying is 100-130°C, the drying time is 24-48 hours, the ceramic coating thickness is 0.5-2μm, and the percentages are mass percentages.
[0012] The high specific energy storage lithium positive electrode material is layered LiCoO2, LiNiO2 and LiNi x Co1-x O2, ternary LiNi 1 / 3 Mn 1 / 3Co 1 / 3 O2 and LiNi 0.85 Co 0.1 Al 0.05 O2, LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnMe) 1-x ]O2 wherein Me = Ni, Co, Fe, sulfur positive electrode, air positive electrode, manganese oxide, vanadium oxide, chromium oxide and one or more combinations of carbon fluoride.
[0013] The high energy density lithium storage positive electrode is prepared by the above-mentioned integrated composite modification method.
[0014] A method for preparing a high-energy-density solid-state battery, using the above-mentioned high-energy-density lithium storage positive electrode, solid electrolyte, and lithium metal negative electrode to prepare the high-energy-density solid-state battery by lamination, comprising the following steps: transferring the electrolyte layer on the release film to the electrode surface, the transfer temperature is 60-100°C, laminating in order the high-energy-density lithium storage positive electrode, the solid electrolyte, and the lithium metal negative electrode, and then forming the battery core by hot pressing, the hot pressing temperature is 80-150°C, the pressure is 100-600MPa, and small molecules are used for interface wetting to form a high-energy-density solid-state battery based on an integrated composite modified positive electrode.
[0015] The preparation method of the solid-state battery electrolyte is as follows: ceramic and polymer are compounded in proportion, dispersed in a solvent to form an electrolyte slurry, the electrolyte slurry is coated on the surface of the release film, and the solvent is dried, wherein the ceramic material is Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 1.3 Ti 1.7 Al 0.3 (PO4)3, Li 10 GeP2S 12 , Li7P2S8I, Li2S-P2S5, Li6PS5Cl; the polymer materials are PVDF, PVDF-HFP, SEBS, NBR (LITFSI), PEO (LiTFSI), and the mass ratio of ceramics to polymer is 1:50-50:1.
[0016] The high-energy-density solid-state battery prepared by the above preparation method.
[0017] The beneficial effects of the present invention are as follows: the present invention constructs an integrated composite modified positive electrode by nano-coating the surface of the positive electrode particles and introducing ceramic materials inside the positive electrode layer and on the surface of the positive electrode layer, and constructs a high-energy-density solid-state battery on this basis, which can solve the problems of poor interfacial ion conductivity, poor thermal stability, serious interfacial side reactions, poor cycle stability caused by lattice oxygen precipitation, and safety hazards existing in the high-energy-density positive electrode, greatly improve the interface performance of the high-energy-density solid-state battery, effectively improve the battery capacity and cycle stability, further enhance the battery safety, and lay the foundation for the practical application of high-energy-density solid-state batteries. The method is simple and easy to implement, and is conducive to large-scale production. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present invention more clear, the present invention is further described in detail. It should be understood that the specific implementation methods described herein are only used to explain the present invention and are not used to limit the present invention.
[0019] The integrated composite modification method of the high specific energy lithium storage positive electrode of the present invention comprises the following steps:
[0020] (1) coating the surface of high specific energy lithium storage cathode material particles with nano-oxide materials;
[0021] (2) blending a ceramic electrolyte inside the coated positive electrode layer to form a composite positive electrode layer;
[0022] (3) A ceramic coating is constructed on the surface of the composite positive electrode layer to form an integrated composite modified high energy density lithium storage positive electrode.
[0023] The nano-oxide coating layer in step (1) is composed of aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), zirconium dioxide (ZrO2), tantalum oxide (LiTaO3, Li3TaO4), Li 1.3 Ti 1.7 Al 0.3 One or more combinations of (PO4)3, the coating method is solid phase method, liquid phase method, ALD method, and the coating layer thickness is 2-50nm.
[0024] The ceramic components in the ceramic electrolyte in step (2) and the ceramic coating in step (3) are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), zirconium dioxide (ZrO2), tantalum oxide (LiTaO3, Li3TaO4), Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li3α La 2 / 3-α TiO3, Li 1.3 Ti 1.7 Al 0.3 (PO4)3, Li 1+β Al β Ge 2-β ( PO4)3, Li 4-δ Ge 1-δ P δ S4, Li7P2S8I, Li2S-P2S5, Li6PS5Cl, one or more combinations thereof, wherein 0.01≤α≤0.33, 0≤β≤0.65, 0≤δ≤1, X=F, Cl, Br, I; the ceramic electrolyte component accounts for 1%-25% of the electrode mass, and the compaction density of the composite electrode after blending is 2.5-3.4g / cm 3 .
[0025] The method for constructing the ceramic coating in step (3) is ultrasonic spraying, the precursor slurry is a ceramic material slurry, the slurry composition is ceramic material, N-methyl-2-pyrrolidone (NMP) solvent and PVDF-HFP glue, the ceramic particle size is 50-500nm, the ceramic content is 3%-7%, and the glue content is 0.5%-2%; the vacuum drying temperature after spraying is 100-130°C, the drying time is 24-48 hours, the ceramic coating thickness is 0.5-2μm, and the percentages are mass percentages.
[0026] The high specific energy storage lithium positive electrode material is layered LiCoO2, LiNiO2 and LiNi x Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3Co 1 / 3 O2 and LiNi 0.85 Co 0.1 Al 0.05 O2, LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnMe) 1-x ]O2 wherein Me = Ni, Co, Fe, sulfur positive electrode, air positive electrode, manganese oxide, vanadium oxide, chromium oxide and one or more combinations of carbon fluoride.
[0027] The high energy density lithium storage positive electrode is prepared by the above-mentioned integrated composite modification method.
[0028] A method for preparing a high-energy-density solid-state battery, using the above-mentioned high-energy-density lithium storage positive electrode, solid electrolyte, and lithium metal negative electrode to prepare the high-energy-density solid-state battery by lamination, comprising the following steps: transferring the electrolyte layer on the release film to the electrode surface, the transfer temperature is 60-100°C, laminating in order the high-energy-density lithium storage positive electrode, the solid electrolyte, and the lithium metal negative electrode, and then forming the battery core by hot pressing, the hot pressing temperature is 80-150°C, the pressure is 100-600MPa, and small molecules are used for interface wetting to form a high-energy-density solid-state battery based on an integrated composite modified positive electrode.
[0029] The preparation method of the solid-state battery electrolyte is as follows: ceramic and polymer are compounded in proportion, dispersed in a solvent to form an electrolyte slurry, the electrolyte slurry is coated on the surface of the release film, and the solvent is dried, wherein the ceramic material is Li 6.4 LqCy 1.4 Ta 0.6 O 12 , Li 1.3 Ti 1.7 Al 0.3 (PO4)3, Li 10 GeP2S 12 , Li7P2S8I, Li2S-P2S5, Li6PS5Cl; the polymer materials are PVDF, PVDF-HFP, SEBS, NBR (LITFSI), PEO (LiTFSI), and the mass ratio of ceramics to polymer is 1:50-50:1.
[0030] The high-energy-density solid-state battery prepared by the above preparation method.
[0031] The present invention is prepared according to the following steps:
[0032] Nano-oxide materials are coated on the surface of the positive electrode material particles, and ceramic electrolytes are blended inside the positive electrode layer to form a composite positive electrode layer. Then, a ceramic coating is constructed on the surface of the composite positive electrode layer to finally form an integrated composite modified positive electrode. The coating methods include solid phase method, liquid phase method, and ALD method. The coating layer thickness is 2-50nm. The blended ceramic component accounts for 1%-25% of the electrode mass, and the compaction density of the composite electrode after blending is 2.5-3.4g / cm 3 The ceramic coating is constructed by ultrasonic spraying. The precursor slurry is a ceramic material slurry. The slurry composition is a ceramic material, N-methyl-2-pyrrolidone (NMP) solvent and PVDF-HFP glue. The ceramic particle size is 50-500nm, the ceramic content is 3%-7%, and the glue content is 0.5%-2%. The thickness of the ceramic coating is 0.5-2μm. The vacuum drying temperature after spraying is 100-130℃, and the drying time is 24-48 hours.
[0033] The present invention adopts an integrated composite modified high specific energy positive electrode, a solid electrolyte, and a lithium metal negative electrode to prepare a high specific energy solid-state battery by lamination. The method of integrated composite modification of the positive electrode is: coating the surface of the positive electrode material particles with nano-oxide materials, then blending the ceramic electrolyte inside the positive electrode layer to form a composite positive electrode layer, and then constructing a ceramic coating on the surface of the composite positive electrode layer to finally form an integrated composite modified positive electrode. Integrated composite modification can improve the thermal stability of the positive electrode, inhibit the problem of oxygen evolution, and improve battery safety.
[0034] The present invention improves the structural stability and thermal stability of the material and inhibits the occurrence of the space charge layer effect by coating the surface of the positive electrode material; by mixing the electrolyte material inside the electrode layer and constructing a ceramic coating on the surface of the pole piece, an ion / electron conduction channel is constructed to solve the problem of difficult ion transmission between the interfaces of solid-state batteries, and at the same time hinder the chemical crosstalk caused by active oxygen precipitation and element diffusion between the positive and negative electrode systems, and prevent the positive and negative electrodes from short-circuiting when the battery system is overheated. Based on this, the construction of a high-performance solid-state battery is achieved through the construction of a solid electrolyte layer and the matching and structural design of the battery core, so as to fully utilize the capacity and improve the safety and reliability of the battery system.
[0035] The present invention coats the surface of the positive electrode material with nano-scale particles, constructs a nano-conductive ceramic coating layer through in-situ reaction, alleviates the volume effect of the material during the charging and discharging process, changes the physical and chemical structure of the surface of the positive electrode material, and effectively improves the electrochemical stability of the positive electrode surface; the design introduces an inorganic solid electrolyte between the particles inside the positive electrode and on the surface of the electrode pole piece, which can enhance the solid-solid interface contact, and at the same time hinder the chemical crosstalk between the positive and negative electrode systems, and prevent the positive and negative electrodes from short-circuiting when the battery system is overheated. The nano-coating, blending and surface coating integrated composite modification technology can simultaneously achieve ion / electron dual conduction between the particles inside the electrode layer and the interface between the electrode / electrolyte layer, regulate and optimize the heterogeneous interface, so that the positive electrode capacity can be fully and stably exerted, and the problem of insufficient capacity exertion and poor cycle stability of solid-state batteries can be improved. This method is simple and easy to implement, suitable for large-scale preparation, and provides a practical way for industrial production.
[0036] Example 1
[0037] (1) Preparation of integrated composite modified positive electrode
[0038] The liquid phase method was used to 0.95 Co 0.02 Mn 0.03 Nano-Li 1.3 Ti 1.7 Al 0.3(PO4)3 coating, the coating thickness is 5nm; the coated material and Li 1.3 Ti 1.7 Al 0.3 (PO4)3 is blended, the ceramic ratio is 5%, and the compaction density of the composite electrode after blending is 3.3g / cm 3 ; Ceramic coating ceramic component is Li 1.3 Ti 1.7 Al 0.3 (PO4)3, particle size is 100nm, coating thickness is 1.5μm, vacuum 100℃ after spraying, and drying for 24 hours. DSC test of the integrated composite modified positive electrode, temperature range is room temperature-500℃, heating rate is 5℃ / min; button cell assembled with integrated composite modified positive electrode, metal lithium, commercial electrolyte and diaphragm is used to test the gram capacity of electrode material, at room temperature, the current density is 450μA / cm 2 , the voltage range is 2.8V-4.4V.
[0039] (2) Preparation of high energy density solid-state batteries
[0040] The ceramic Al2O3 and NBR (LiTFSI) are dispersed in a solvent to form an electrolyte slurry, and the electrolyte slurry is coated on the surface of the release film. The solvent is dried, and the electrolyte layer on the release film is transferred to the electrode surface. The transfer temperature is 100°C. In a dry room with an ambient humidity of 0.5%, the integrated composite modified positive electrode, solid electrolyte, and lithium metal negative electrode are stacked in order, and the battery cell is formed by hot pressing. The hot pressing temperature is 100°C and the pressure is 300MPa. Small molecules are used for interface wetting. The current is 0.2A, and the voltage range of the cycle test is 3.0-4.4V.
[0041] Example 2
[0042] (1) Preparation of integrated composite modified positive electrode
[0043] The liquid phase method was used to 0.95 Co 0.02 Mn 0.03 The surface of the O2 positive electrode material particles is coated with nano-Li3PO4, and the coating layer thickness is 8nm; the coated material is blended with Li6PS5Cl, and the ceramic ratio is 15%. After blending, the compaction density of the composite electrode is 3.2g / cm 3; The ceramic coating is Li2S-P2S5, the particle size is 200nm, the coating thickness is 2μm, and the vacuum is 80℃ after spraying and dried for 24 hours. The integrated composite modified positive electrode is tested by DSC, the temperature range is room temperature-500℃, and the heating rate is 5℃ / min; the button cell assembled with the integrated composite modified positive electrode, metal lithium, commercial electrolyte and diaphragm is used to test the gram capacity of the electrode material. At room temperature, the current density is 450μA / cm 2 , the voltage range is 2.8V-4.4V.
[0044] (2) Preparation of high energy density solid-state batteries
[0045] The ceramic Li6PS5Cl and SEBS are dispersed in a solvent to form an electrolyte slurry, which is then coated on the release film surface, the solvent is dried, and the electrolyte layer on the release film is transferred to the electrode surface at a transfer temperature of 100°C. In a dry room with an ambient humidity of 0.5%, the integrated composite modified positive electrode, solid electrolyte, and lithium metal negative electrode are stacked in sequence, and then the battery cell is formed by hot pressing at a temperature of 100°C and a pressure of 200MPa, and small molecules are used for interface wetting. The current is 0.2A, and the voltage range of the cycle test is 3.0-4.4V.
[0046] Comparative Example 1
[0047] Using LiNi 0.95 Co 0.02 Mn 0.03 O2 cathode material for electrode preparation, compaction density is 3.3g / cm 3 The positive electrode was subjected to DSC test at a temperature range of room temperature to 500°C and a heating rate of 5°C / min. The electrode material gram capacity was tested by assembling a button cell with a positive electrode, metal lithium, commercial electrolyte and separator. At room temperature, the current density was 450μA / cm 2 , the voltage range is 2.8V-4.4V.
[0048] After stacking the positive electrode, separator, and lithium metal negative electrode in order, they were injected with liquid and then the battery performance was tested. The current was 0.2A and the voltage range of the cycle test was 3.0-4.4V.
[0049] Comparative Example 2
[0050] Using LiNi 0.95 Co 0.02 Mn 0.03 O2 cathode material for electrode preparation, compaction density is 3.3g / cm 3The positive electrode was subjected to DSC test at a temperature range of room temperature to 500°C and a heating rate of 5°C / min. The electrode material gram capacity was tested by assembling a button cell with a positive electrode, metal lithium, commercial electrolyte and separator. At room temperature, the current density was 450μA / cm 2 , the voltage range is 2.8V-4.4V.
[0051] The ceramic Al2O3 and NBR (LiTFSI) are dispersed in a solvent to form an electrolyte slurry, and the electrolyte slurry is coated on the surface of the release film. The solvent is dried, and the electrolyte layer on the release film is transferred to the electrode surface. The transfer temperature is 100°C. In a dry room with an ambient humidity of 0.5%, the integrated composite modified positive electrode, solid electrolyte, and lithium metal negative electrode are stacked in order, and the battery cell is formed by hot pressing. The hot pressing temperature is 100°C and the pressure is 300MPa. Small molecules are used for interface wetting. The current is 0.2A, and the voltage range of the cycle test is 3.0-4.4V.
[0052] Table 1 is a comparison of the electrode and battery performance in Examples 1-2 of the present invention and the comparative example.
[0053] Table 1
[0054] Positive electrode DCS thermal decomposition starting temperature ℃ Gram capacity mAh / g Example 1 221 223 Example 2 230 220 Comparative Example 1 203 221 Comparative Example 2 203 183
[0055] The DSC test results show that the thermal stability of the positive electrode modified by the integrated composite is significantly improved, and the starting temperature of thermal decomposition is increased by 20℃-30℃ compared with the unmodified system; in addition, the introduction of the integrated composite modified positive electrode effectively improves the ion / electron transport capacity inside the electrode layer and at the interface between layers. The electrode in the solid-state battery system still exerts a gram capacity similar to that of the electrolyte system (Comparative Example 1). Compared with the solid-state battery system using a positive electrode that has not undergone integrated composite modification (Comparative Example 2), the gram capacity is increased by 20%.
[0056] The application of high-energy-density positive electrodes provides the basis for obtaining high-energy-density solid-state batteries. The high-energy-density positive electrodes modified by integrated composites face problems such as poor interface ion conductivity, poor thermal stability, serious interface side reactions, poor cycle stability caused by lattice oxygen precipitation, and potential safety hazards. The present invention constructs an integrated composite modified positive electrode by nano-coating the surface of positive electrode particles and introducing ceramic materials inside the positive electrode layer and on the surface of the positive electrode layer. On this basis, a high-energy-density solid-state battery is constructed, which greatly improves the interface performance of the high-energy-density solid-state battery, effectively improves the battery capacity and cycle stability, further enhances the battery safety, and lays the foundation for the practical application of high-energy-density solid-state batteries.
[0057] This method is simple and easy to implement, suitable for large-scale preparation, and provides a practical way for industrial production. It can be applied to fields such as drones and electric vehicles that have higher requirements for energy storage battery endurance, safety and reliability.
[0058] The embodiments described above are only used to illustrate the technical ideas and features of the present invention, and their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. The patent scope of the present invention cannot be limited only by this embodiment, that is, any equivalent changes or modifications made to the spirit disclosed by the present invention still fall within the patent scope of the present invention.
Claims
1. An integrated composite modification method for a high specific energy lithium storage positive electrode, characterized in that: The following steps are involved: (1) coating the surface of high specific energy lithium storage cathode material particles with nano-oxide materials; (2) blending a ceramic electrolyte inside the coated positive electrode layer to form a composite positive electrode layer; (3) A ceramic coating is constructed on the surface of the composite positive electrode layer to form an integrated composite modified high energy density lithium storage positive electrode.
2. The integrated composite modification method of the high specific energy lithium storage positive electrode according to claim 1, characterized in that: The nano-oxide coating layer in step (1) is composed of aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), zirconium dioxide (ZrO2), tantalum oxide (LiTaO3, Li3TaO4), Li 1.3 Ti 1.7 Al 0.3 One or more combinations of (PO4)3, the coating method is solid phase method, liquid phase method, ALD method, and the coating layer thickness is 2-50nm.
3. The integrated composite modification method of the high specific energy storage lithium positive electrode according to claim 1, characterized in that: The ceramic components in the ceramic electrolyte in step (2) and the ceramic coating in step (3) are aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), lithium phosphate (Li3PO4), zirconium dioxide (ZrO2), tantalum oxide (LiTaO3, Li3TaO4), Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 3α La 2 / 3-α TiO3, Li 1.3 Ti 1.7 Al 0.3 (PO4)3, Li 1+β Al β Ge 2-β( PO4)3, Li 4-δ Ge 1-δ P δ S4, Li7P2S8I, Li2S-P2S5, Li6PS5Cl, one or more combinations thereof, wherein 0.01≤α≤0.33, 0≤β≤0.65, 0≤δ≤1, X=F, Cl, Br, I; the ceramic electrolyte component accounts for 1%-25% of the electrode mass, and the compaction density of the composite electrode after blending is 2.5-3.4g / cm 3 .
4. The integrated composite modification method of the high specific energy storage lithium positive electrode according to claim 1, characterized in that: The method for constructing the ceramic coating in step (3) is ultrasonic spraying, the precursor slurry is a ceramic material slurry, the slurry composition is ceramic material, N-methyl-2-pyrrolidone (NMP) solvent and PVDF-HFP glue, the ceramic particle size is 50-500nm, the ceramic content is 3%-7%, and the glue content is 0.5%-2%; the vacuum drying temperature after spraying is 100-130°C, the drying time is 24-48 hours, the ceramic coating thickness is 0.5-2μm, and the percentages are mass percentages.
5. The integrated composite modification method of the high specific energy storage lithium positive electrode according to claim 1, characterized in that: The high specific energy storage lithium positive electrode material is layered LiCoO2, LiNiO2 and LiNi x Co 1-x O2, ternary LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and LiNi 0.85 Co 0.1 Al 0.05 O2, LiNi 0.95 Co 0.02 Mn 0.03 O2, spinel LiMn2O4, 5V spinel LiNi 0.5 Mn 1.5 O4, phosphate LiMPO4 where M = Fe, Mn, lithium-rich manganese-based positive electrode material Li[Li x (MnMe) 1-x ]O2 wherein Me = Ni, Co, Fe, sulfur positive electrode, air positive electrode, manganese oxide, vanadium oxide, chromium oxide and one or more combinations of carbon fluoride.
6. A high specific energy lithium storage positive electrode prepared by the integrated composite modification method according to any one of claims 1 to 5.
7. A method for preparing a high specific energy solid-state battery, characterized in that: A high-energy-density solid-state battery prepared by lamination using the high-energy-density lithium storage positive electrode, solid-state electrolyte, and lithium metal negative electrode as described in claim 6 comprises the following steps: transferring the electrolyte layer on the release film to the electrode surface at a transfer temperature of 60-100°C, laminating the high-energy-density lithium storage positive electrode, solid-state electrolyte, and lithium metal negative electrode in order, and then forming the battery cell by hot pressing at a hot pressing temperature of 80-150°C and a pressure of 100-600MPa, using small molecules for interface wetting to form a high-energy-density solid-state battery based on an integrated composite modified positive electrode.
8. The method for preparing a high specific energy solid-state battery according to claim 7, characterized in that: The preparation method of the solid-state battery electrolyte is as follows: ceramic and polymer are compounded in proportion, dispersed in a solvent to form an electrolyte slurry, the electrolyte slurry is coated on the surface of the release film, and the solvent is dried, wherein the ceramic material is Li 6.4 Ln3Z 1.4 Ta 0.6 O 12 , Li 1.3 Ti 1.7 Al 0.3 (PO4)3, Li 10 GeP2S 12 , Li7P2S8I, Li2S-P2S5, Li6PS5Cl; the polymer materials are PVDF, PVDF-HFP, SEBS, NBR (LITFSI), PEO (LiTFSI), and the mass ratio of ceramics to polymer is 1:50-50:
1.
9. A high-energy-density solid-state battery prepared by the preparation method as claimed in claim 7 or 8.
Citation Information
Patent Citations
Positive plate of lithium-ion battery with high safety performance and fabrication method of positive plate
CN105449159A
Lithium ion battery piezoelectric positive electrode composite pole piece and lithium ion battery application thereof
CN106876660A
Thermochemical blocking type composite positive electrode material, positive electrode plate and preparation method therefor, and lithium ion battery
CN107146875A
Positive electrode of solid electrolyte and solid state battery
CN108878960A
Positive electrode plate and polymer electrolyte membrane combined piece and preparation method thereof
CN110323493A